PulsePath - Elfving, Mårten; Lundqvist, Karl (My University, 2023)
The use of visual feedback for navigation while motorcycling poses a significant risk as it diverts the rider’s attention from the traffic situation, compromising their safety as any visual aversion longer than two seconds significantly increases the risk of accidents. This master’s thesis presents the design and evaluation of a prototype for an integrated vibro-tactile navigation interface aimed at addressing this challenge. The study involved the development of a prototype that effectively communicated directional information for navigation events such as turns and roundabouts. Since the act of motorcycling in itself can be an equally, if not more, important when choosing to travel with a motorcycle, a user-centered approach was adopted to consider the hedonic and joyful aspects of motorcycling in addition to the safety requirements. The user experience, or UX, was examined using Marc Hassenzahl’s hedonic/pragmatic model of user experience [5] as it can encompass all aspects of motorcycling. The prototype was evaluated with a sample of 10 participants in a real-world setting, with the objective to assess the impact on vehicle control, cognitive workload and riding experience during navigation tasks. The results showed no substantial negative effects on vehicle control, indicating the effectiveness of the vibro-tactile navigation interface in maintaining rider control while simultaneously receiving navigation guidance. Moreover, the participants reported a decrease in cognitive workload, as the vibro-tactile feedback enabled them to focus more on the riding experience rather than being distracted by visual navigation aids. The findings regarding the UX demonstrated that the integration of vibro-tactile feedback enhanced the overall hedonic aspects of motorcycling, as it allowed the riders to immerse themselves fully in the riding experience. Furthermore, the use of vibro-tactile cues contributed to a heightened sense of safety by enabling riders to maintain their visual focus on the traffic situation while still receiving reliable navigation information. The outcomes of this research contribute to the field of motorcycle navigation interfaces and highlight the potential of vibro-tactile technology in enhancing safety and rider experience. The findings emphasize the importance of multimodal interfaces that include haptic feedback, paving the way for future advancements in the design of motorcycle navigation systems that prioritize safety, usability, and the user experience.
Keywords: User Experience; Navigation; Motorcycling; Electric Vehicles; Haptic Feedback; HCI; Transportation; User-Centered Design; Traffic Safety; Multimodal Interfaces